Micro-computed tomography analysis and ex-vivo detection of six root canals in a four-rooted mandibular first premolar - Hany Mohamed Aly Ahmed; Mohideen Salihu Farook (BMC Oral Health)
Abstract Background Mandibular first premolar teeth show a wide range of root and canal anatomical variations including accessory roots, deep root proximal grooves and multiple canals. This study provides qualitative and quantitative morphological analysis of a rare four-rooted mandibular first premolar scanned using micro-CT. In addition, it provides clinical implications through endodontic access cavity preparation and negotiation of canals under dental operating microscope (DOM) to assess the difficulty for locating the canals. Methods An extracted four-rooted mandibular first premolar tooth sample was subjected to 2D radiographic imaging in two views and micro-computed tomography (micro-CT) scanning with a resolution of 25 μm. Subsequently, 3D- reconstruction of the tooth sample was performed using Mimics software (Materialise, Leuven, Belgium). 3D (volume and surface area) and 2D measurements (distances between orifices, area, perimeter, maximum and minimum diameter, roundness, aspect ratio and form factor) were obtained. In addition, endodontic access was prepared, and the canals were explored under the DOM. Location of the canals were confirmed by periapical radiographs with the aid of hand files. Results The 2D imaging showed the presence of four canals. Micro-CT analysis showed a complex canal anatomy which was classified using Ahmed et al. coding system as 444 MB1–2–1–2 DB2-1-2-1-3-2-3 1(ML1 DL1). Quantitative analysis showed that the MB root had the highest canal volume and surface area compared to other canals. The 2D measurements showed wide variations among canals, which reflects the complexity of the canals in terms of size and geometry. The MB and DB canals tend to have more aspect ratio values (more oval/flattened) than other canals. After access cavity preparation and exploration, six root canals were identified [mesio-buccal one (MB1), mesio-buccal two (MB2), disto-buccal (DB), mesio-lingual (ML), disto-lingual (DL) and lingual disto-buccal (LDB)]. The canals in the MB root showed two locations of splitting. Conclusions Mandibular first premolars may have complex variations in the number of roots and canal configurations. The different anatomical presentations demonstrated in the 2D and 3D measurements of the six canals presented in this report signifies the anatomical variabilities, which could complicate the detection and negotiation of canals during root canal treatment. Ahmed et al. coding system is useful in classifying teeth with complex root and canal anatomy.